2017
DOI: 10.1111/nep.12836
|View full text |Cite
|
Sign up to set email alerts
|

Primacy of lowered baseline glomerular filtration rate as a risk for incident chronic kidney disease: A longitudinal study in Japanese subjects

Abstract: Seven risk factors for incident CKD were identified in Japanese health examinees. However, lowered baseline eGFR outweighed other risks to the degree that eGFR alone was suffice for CKD prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Only 2 cohort studies evaluated CKD onset; therefore, we could not perform a quantitative analysis. 46,47 We performed univariate meta-regression to evaluate the association between risk of low eGFR due to an increment of 1 kg/m 2 BMI and mean baseline BMI. To include subjects who were more homogeneous in the analysis, we analyzed only studies on an Asian Pacific population because there were an adequate number of studies, and we found a significant increase in the effect size with an increasing mean baseline BMI (Supplementary Figure S7).…”
Section: Bmi and Development Of Ckd De Novomentioning
confidence: 99%
“…Only 2 cohort studies evaluated CKD onset; therefore, we could not perform a quantitative analysis. 46,47 We performed univariate meta-regression to evaluate the association between risk of low eGFR due to an increment of 1 kg/m 2 BMI and mean baseline BMI. To include subjects who were more homogeneous in the analysis, we analyzed only studies on an Asian Pacific population because there were an adequate number of studies, and we found a significant increase in the effect size with an increasing mean baseline BMI (Supplementary Figure S7).…”
Section: Bmi and Development Of Ckd De Novomentioning
confidence: 99%
“…Recent studies have shown rituximab (RTX) to be a safe CS sparing therapy in difficult-to-treat SDNS. 1 Bruchfeld et al reported remission (complete remisssion (CR) or partial remission) in 15 of 16 adult patients with steroid dependent minimal change disease (MCD) with RTX therapy. 1 Ruggenenti et al 2 reported favourable response to RTX therapy in patients (both adult and children) with steroid dependent MCD/focal segmental glomerulosclerosis (FSGS)/ mesangioproliferative glomerulonephritis.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…
Miyakoshi et al 1 conducted a prospective study of risk factors for incident chronic kidney disease (CKD) in 17 153 healthy subjects. CKD was defined as estimated glomerular filtration rate (eGFR) <60 mL/min per 1.73 m 2 or positive dipstick proteinuria.
…”
mentioning
confidence: 99%